Enhanced magnetic separation and photocatalytic activity of nitrogen doped titania photocatalyst supported on strontium ferrite - Aziz, A.A.; Yong, K.S.; Ibrahim, S.; Pichiah, S. (2012)
An enhanced ferromagnetic property, visible light active TiO 2 photocatalyst was successfully synthesized by supporting strontium ferrite (SrFe 12O 19) onto TiO 2 doped with nitrogen (N) and compared with N-doped TiO 2. The synthesized catalysts were further characterized with X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive X-ray spectroscopy (EDS), BET surface area analysis, vibrating sample magnetometer (VSM), X-ray photon spectroscopy (XPS) and visible light spectroscopy analysis for their respective properties. The XRD and EDS revealed the structural and inorganic composition of N-TiO 2 supported on SrFe 12O 19. The supported N-TiO 2 exhibited a strong ferromagnetic property with tremendous stability against magnetic property losses. It also resulted in reduced band gap (2.8eV) and better visible light absorption between 400 and 800nm compared to N-doped TiO 2. The photocatalytic activity was investigated with a recalcitrant phenolic compound namely 2,4-dichlorophenol (2,4-DCP) as a model pollutant under direct bright and diffuse sunlight exposure. A complete degradation of 2,4-DCP was achieved with an initial concentration of 50mg/L for both photocatalysts in 180min and 270min respectively under bright sunlight. Similarly the diffuse sunlight study resulted in complete degradation for supported N-TiO 2 and >85% degradation N-TiO 2, respectively. Finally the supported photocatalyst was separated under permanent magnetic field with a mass recovery ∼98% for further reuse. © 2011 Elsevier B.V.